Gene Editing for the Treatment of Alzheimer’s Disease: A Comprehensive Review - Haider Abdullah Alsanawi et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Abstract Alzheimer’s disease (AD) is a progressive neurodegenerative condition characterized by cognitive impairment, memory loss, and significant functional decline. Current treatment strategies focus on symptom management but do not target the disease's underlying genetic and molecular causes. Gene editing, particularly the CRISPR-Cas9 system, has emerged as a transformative tool to modify genetic pathways implicated in AD, including those related to amyloid-beta accumulation, tau hyperphosphorylation, and apolipoprotein E (APOE) polymorphisms. This review discusses the potential applications of gene editing in AD treatment, preclinical advancements, challenges in implementation, and the ethical considerations surrounding this innovative therapeutic strategy. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/272 https://doi.org/10.5281/zenodo.14480412